A decentralized power injection-based approach for voltage imbalance mitigation in three-phase distribution networks - Saatong Kenfack Tsobze; Wulfran Fendzi Mbasso; Ambe Harrison; Mohammad Khishe; Idriss Dagal; Pradeep Jangir; Aseel Smerat; Saad F. Al-Gahtani; Z. M. S. Elbarbary (Scientific Reports)
Abstract This voltage imbalance in four-wire, three-phase distribution networks gives rise to negative-sequence and zero-sequence voltage components which increases the total apparent power received from the network. This also increases the energy losses from the network. Traditional methods employed for load compensation provide partial fixes at the local area without any form of system-wide solution. This work presents a new decentralized control strategy for the inverter of a photovoltaic-based three-phase power source (DPS) aimed at instantaneously correcting phase voltage imbalances. The method does not require load current measurement because it depends entirely on real-time voltage measurements at the point of common coupling (PCC). The capability to mitigate the unbalance depends on the available power of the DPS. To test how effective the proposed method is, simulations have been conducted using MATLAB/SIMULINK on a distribution network with a four-leg inverter connected to a line with cascading single and three-phase loads, where a four-leg inverter enables independent phase control and mitigation of neutral current disturbances. The results show that this control enables the comparison of balancing for three-phase powers with a 96.4% improvement. The phase-to-phase voltage deviation was also reduced by around 8 V (3.6% of nominal voltage). Furthermore, the total harmonic distortion (THD) of the output current from the inverter did not rise about 3.75%, hence improving the power quality. Its real-time applicability in decentralized renewable energy integration is possible due to the method’s effectiveness in reducing voltage imbalances even when network conditions are extremely distorted.